2013
DOI: 10.1002/eqe.2366
|View full text |Cite
|
Sign up to set email alerts
|

Model‐based multi‐metric control of uniaxial shake tables

Abstract: SUMMARY Shake tables provide a direct means by which to evaluate structural performance under earthquake excitation. Because the entire structure is mounted on the base plate and subjected to the ground motion in real time, dynamic effects and rate‐dependent behavior can be accurately represented. Shake table control is not straightforward as the desired signal is an acceleration record, while most actuators operate in displacement feedback for stability. At the same time, the payload is typically large relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 17 publications
0
56
0
Order By: Relevance
“…Since shake tables use hydraulic actuators to produce motion, this compatibility requires high performance acceleration tracking of shake tables. While this is a challenging issue, there has been significant progress in the enhancement of acceleration tracking of shake tables [namely: Stehman and Nakata (2012) and Phillips et. al.…”
Section: Compatibility Conditions For Dynamic Equivalencementioning
confidence: 99%
“…Since shake tables use hydraulic actuators to produce motion, this compatibility requires high performance acceleration tracking of shake tables. While this is a challenging issue, there has been significant progress in the enhancement of acceleration tracking of shake tables [namely: Stehman and Nakata (2012) and Phillips et. al.…”
Section: Compatibility Conditions For Dynamic Equivalencementioning
confidence: 99%
“…In Stoten [1], it was found that the corresponding minimum order could be n = 2 or 3, depending upon the CF; hence, the order is now fixed as n = 3 for all CF. Accordingly, the sum of terms on the left-hand side of both (8) and (9) is required to be equal to a third-order monic transfer function defined by:…”
Section: Transformation Of a Proper N Th -Order Transfer Function Intmentioning
confidence: 99%
“…Examples of modified DAC strategies, which incorporate methods of circumventing the low frequency control and drift problems, include high fidelity adaptive control [5], acceleration feedforward control with displacement feedback via Kalman filter estimation [6], control augmentation via force feedback [7] and feedforward control with multi-metric feedback [8]. One advantage of DAC is that it allows good fidelity of signal resolution at high frequencies, compared with (say) the resolution provided by a conventional displacement control strategy.…”
Section: An Indirect Acceleration Control Strategy For Shaking Tablesmentioning
confidence: 99%
“…The use can be traced back to the first hand-powered table created in the 19th century [1]. These challenges become more problematic when a specimen exhibits nonlinear behavior and its mass is large relative to that of the table [3]. Although the testing capacity has been greatly improved, high-fidelity shake table control remains to be challenging because of several difficulties such as the inherent hydraulic actuator nonlinearity and control-structure interaction (CSI) effects [2].…”
Section: Introductionmentioning
confidence: 99%
“…A controller that deals with nonlinearity of shake table dynamics and CSI is needed. Moreover, it was difficult to preserve the stability of a shake table acceleration tracking control by acceleration feedback alone [3]; hence, displacement-based shake table control gained popularity. Spencer and Yang [4] adopted a linearized shake table model (a transfer function) to describe the relationship of command signals and measured acceleration.…”
Section: Introductionmentioning
confidence: 99%